Effect of Food Subsidies on Micronutrient Consumption. Issue 3 (December 2016) - Muchomba, Felix M.; Kaushal, Neeraj
In this article, we study the effect of an exogenous increase in wheat and rice price subsidy to poor families resulting from a targeted food price subsidy programme in India called the Targeted Public Distribution System (TPDS) on micronutrient intake in low-income families. Descriptive results show that wheat and rice have one of the lowest micronutrient density scores, suggesting that these are poor suppliers of micronutrients. Empirical analysis suggests that the increase in monthly per capita subsidy amount of ₹15–18 resulting from the TPDS expansion lowered calcium intake by 12–14 per cent and had negligible to small (often negative) effects on the consumption of most micronutrients.